Bridging the gap – A database tool for BIM-based circularity assessment. Issue 1 (1st September 2022) - Göswein, V; Carvalho, S; Lorena, A; Fernandes, J; Ferrão, P
Abstract: The concept of circular economy attracts attention across sectors. Since construction materials are the single largest material stock and flow, there is a particular interest from research and policy to apply the circularity concept to buildings. Large quantities of construction and demolition waste end up in landfill, despite new EU legislation that requires a 70% recovery rate. There is a gap between this ambitious goal and the reality of the construction industry. Building Information Modelling (BIM) has the potential to improve building design and construction processes for an increased recovery of materials. However, insufficient data, inconsistent methods and interoperability issues inhibit BIM application to unfold its full potential in circularity assessments. This paper introduces the CirBIM database framework. It provides BIM users with the required robust data to improve the circularity throughout the building's life cycle: from the design phase throughout renovation activities to the end-of-life stage. The paper proposes a new workflow of building circularity assessment, describe the architecture of the new database tool, and recommends relevant data sources and information models to streamline data mining processes. The new database tool is exemplified through application to a case study building in Portugal, emphasizing the need for different metrics and the need of integration of the end-of-life scenarios in the building design stage.